White matter abnormalities in Parkinson's disease patients with glucocerebrosidase gene mutations. Issue 6 (15th February 2013) - Agosta, Federica; Kostic, Vladimir S.; Davidovic, Kristina; Kresojević, Nikola; Sarro, Lidia; Svetel, Marina; Stanković, Iva; Comi, Giancarlo; Klein, Christine; Filippi, Massimo
ABSTRACT Glucocerebrosidase gene mutations represent a genetic risk factor for the development of Parkinson's disease. This study investigated brain alterations in Parkinson's disease patients carrying heterozygous glucocerebrosidase gene mutations using structural and diffusion tensor magnetic resonance imaging. Among 360 Parkinson's disease patients screened for glucocerebrosidase gene mutations, 19 heterozygous mutation carriers (5.3%) were identified. Of these, 15 patients underwent a neuropsychological evaluation and a magnetic resonance imaging scan. Sixteen age‐ and sex‐matched healthy controls and 14 idiopathic Parkinson's disease patients without glucocerebrosidase gene mutations were also studied. Tract‐based spatial statistics was used to perform a white matter voxel‐wise analysis of diffusion tensor magnetic resonance imaging metrics. Mean fractional anisotropy values were obtained from white matter tracts of interest. Voxel‐based morphometry was used to assess gray‐matter atrophy. Cognitive deficits were found in 9 mutation carrier patients (60%). Compared with controls, Parkinson's disease patients carrying glucocerebrosidase gene mutations showed decreased fractional anisotropy in the olfactory tracts, corpus callosum, and anterior limb of the internal capsule bilaterally, as well as in the right anterior external capsule, and left cingulum, parahippocampal tract, parietal portion of the superior longitudinal fasciculus, and occipital white matter. Mutation carrier patients also had decreased fractional anisotropy of the majority of white matter tracts compared with Parkinson's disease patients with no mutations. No white matter abnormalities were found in Parkinson's disease patients without glucocerebrosidase gene mutations. No gray matter difference was found between patients and controls. In Parkinson's disease patients, verbal fluency scores correlated with white matter abnormalities. Parkinson's disease patients carrying glucocerebrosidase gene mutations experience a distributed pattern of white matter abnormalities involving the interhemispheric, frontal corticocortical, and parahippocampal tracts. White matter pathology in these patients may have an impact on the clinical manifestations of the disease, including cognitive impairment. © 2013 Movement Disorder Society